An Examination of the relationship between Health and Economic Growth - Garima Malik (Indian Council for Research on International Economic Relations (ICRIER), 2006)
This paper attempts to examine the relationship between health and economic growth. The rate of growth is measured using gross national income [GNI] and health status is measured using infant mortality rate, life expectancy rate and crude health rate. The above relationships are measured using a multivariate framework controlling for other background variables. Thus we have modelled the macroeconomic impact of health. A theoretical framework has been developed to model this linkage between health and growth and this is further tested using a regression model which tests the causality between these variables of interest. These models are tested using pooled data. We have also assumed in this analysis that these variables are affected by state-specific unobservable fixed effects, since there are other cultural, political and social factors at work here.
Keywords: I12; C21; O40; 330; Health; Economic Growth